From the Apollo programme to the EM algorithm and beyond. Issue 4 (28th July 2021) - Laird, Nan; Hirschland, Edward C.
Abstract : Nan Laird is the Harvey V. Fineberg professor of biostatistics (emerita) at the Harvard T. H. Chan School of Public Health, and the winner of the 2021 International Prize in Statistics. In this interview with Ed Hirschland, she discusses her career and contributions Abstract :